2010
DOI: 10.1128/iai.00473-09
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Combination of Three Pneumococcal Proteins Confers Additive and Broad Protection against Streptococcus pneumoniae Infections in Mice

Abstract: Pneumococcal polysaccharide-based vaccines are effective in preventing pneumococcus infection; however, some drawbacks preclude their widespread use in developing and undeveloped countries. Here, we evaluated the protective effects of ATP-dependent caseinolytic protease (ClpP), pneumolysin mutant (⌬A146 Ply), putative lipoate-protein ligase (Lpl), or combinations thereof against pneumococcal infections in mice. Vaccinated mice were intraperitoneally and/or intranasally challenged with different pneumococcal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
3
37
0
2
Order By: Relevance
“…Serum passive transfer studies have revealed the protective property of antigen-specific IgG in controlling pneumococcal diseases (26,34). Also, it is well known that IgA is an important immunoglobulin with anti-inflammatory properties (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum passive transfer studies have revealed the protective property of antigen-specific IgG in controlling pneumococcal diseases (26,34). Also, it is well known that IgA is an important immunoglobulin with anti-inflammatory properties (45).…”
Section: Discussionmentioning
confidence: 99%
“…The ⌬A146Ply (full-length wild-type Ply with a deletion of A146) gene was constructed by using site-directed mutagenesis by overlap extension in our previous study (30). It was then cloned, expressed, and purified as described in the previous studies (26,30). The full-length DnaJ gene was PCR amplified from the TIGR4 strain using two pairs of primers: F-DnaJ-N plus RDnaJ-N and F-DnaJ-C plus R-DnaJ-C (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were immunized according to the protocol described in a previous study [44], with slight modifications. Briefly, separate formulations of the His 6 -tagged VncS antigen and the commercially available synthetic Pep27 peptide (ProSci Inc, USA) were prepared using aluminum hydroxide (Alum) as an adjuvant, in the ratio 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the primers used are listed in Table S2 in the supplemental material. The rafX and lgt genes were deleted from the chromosome of S. pneumoniae by insertion-deletion mutagenesis, which was performed essentially according to an established protocol (25). For example, upstream and downstream fragments of the rafX gene were PCR amplified with primers rafX UP P1-2 and rafX DW P3-4, respectively.…”
Section: Methodsmentioning
confidence: 99%